Ответы и объяснения

2014-02-03T18:17:54+04:00
-у=-10-3х                                                                  х²-40х-12х²-(100+60х+9х²)+20=0x^2-4xy-y^2=-20                                                       х²-40х-12х²-100-60х-9х²+20=0                                                                                  -20х²-100х-80=0(/-20)у=10+3х                                                                    х²+5х+4=0x^2-4x(10+3х)-(10+3х)^2=-20                               D=25-4*4=9                                                                                   x=(-5+3)/2=-1                                                                                  x=(-5-3)/2=-4х=-1                х=-1у=10+3*(-1)  у=7х=-4                х=-4у=10+3*(-4)  у=-2                                       ОТВЕТ: (-1;7);(-4;2)